SEPULUH PILAR MENUJU GEREJA YANG SEHAT - Sampitmo Habeahan; Delilitnaria Tarigan (Jurnal Christian Humaniora, 2021)
Abstract Jesus Christ has prophesied the presence of church. The church is a collection of believers who have received salvation. Refers to the fact that He wants His job done perfectly same as He is perfect too. Have the local churches exemplified the early Christian way of life in faith and service? Because Jesus Christ has built the church and given His words therefore the church should be healthy. However, the fact that there are many churches aren’t healthy where it can be seen there is no growth in quality and quantity. The objective of this research is to dig what pillars of healthy church based on the bible is. The method of this research is literature study. The result of this research is described to ten pillars towards the health of church as follows : 1. Centered on the God’s word; 2. Epository sermons; 3. Making discipleship; 4. Doing evangelism; 5. Praying church; 6. The church involving the laity; 7. A vision – driven church; 8. The church on the mission; 9. The balance of multiple divine mandates ; 10. Maintaining the holiness.Key words: Pillar, the healthy church